2019
DOI: 10.1111/1440-1630.12574
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cognitive strategy use common in children with reduced social competence derived from parent perceptions

Abstract: Introduction: Occupational therapists are increasingly being referred children who experience reduced social competence. Ineffective use of cognitive strategies during social interactions is known to contribute to reduced social competence in children who have difficulty learning. Little is known about the nature of social cognitive strategy use or how it may be observed in children during performance of school occupations. This study aimed to explore the type of difficulties in cognitive strategy use that chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The main aim of this study was to analyze the effect of a self-regulation program at a primary school on the social interactions of children with special educational needs and neurotypical children from the teachers’ and parents’ perspectives. This objective has become increasingly important in referrals made to occupational therapists in recent years [ 23 ]. In fact, some studies have indicated that children with low social skills showed difficulties in emotional regulation, and this factor should be considered in interventions performed by occupational therapists [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of this study was to analyze the effect of a self-regulation program at a primary school on the social interactions of children with special educational needs and neurotypical children from the teachers’ and parents’ perspectives. This objective has become increasingly important in referrals made to occupational therapists in recent years [ 23 ]. In fact, some studies have indicated that children with low social skills showed difficulties in emotional regulation, and this factor should be considered in interventions performed by occupational therapists [ 9 ].…”
Section: Discussionmentioning
confidence: 99%